Labor Market Institutions, Fiscal Multipliers, and Macroeconomic Volatility - Maximilian Boeck; Jesús Crespo Cuaresma; Christian Glocker (Center for Economic Studies and ifo Institute (CESifo), 2022)
We study empirically how various labor market institutions – (i) union density, (ii) unemployment benefit remuneration, and (iii) employment protection – shape fiscal multipliers and output volatility. Our theoretical model highlights that more stringent labor market institutions attenuate both fiscal spending multipliers and macroeconomic volatility. This is validated empirically by an interacted panel vector autoregressive model estimated for 16 OECD countries. The strongest effects emanate from employment protection, followed by union density. While some labor market institutions mitigate the contemporaneous impact of shocks, they, however, reinforce their propagation mechanism. The main policy implication is that stringent labor market institutions render cyclical fiscal policies less relevant for macroeconomic stabilization.
Keywords: E62; C33; J21; J38; 330; fiscal policy; fiscal multipliers; labor market institutions; interacted panel VAR